2005
DOI: 10.1016/j.jacc.2005.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Acute Consumption of Flavanol-Rich Cocoa and the Reversal of Endothelial Dysfunction in Smokers

Abstract: The circulating pool of bioactive NO and endothelium-dependent vasodilation is acutely increased in smokers following the oral ingestion of a flavanol-rich cocoa drink. The increase in circulating NO pool may contribute to beneficial vascular health effects of flavanol-rich food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
212
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(241 citation statements)
references
References 48 publications
18
212
0
6
Order By: Relevance
“…Other investigators have observed favorable vascular effects of black and green tea [58,59]. As outlined in the Table 1, improved endothelial function has also been demonstrated following consumption of other flavonoid-containing beverages and foods, including grape juice [49,60] wine, [61], dealcoholized red wine [62], cocoa [63][64][65], and chocolate [66].…”
Section: Flavonoids and Endothelial Functionmentioning
confidence: 91%
“…Other investigators have observed favorable vascular effects of black and green tea [58,59]. As outlined in the Table 1, improved endothelial function has also been demonstrated following consumption of other flavonoid-containing beverages and foods, including grape juice [49,60] wine, [61], dealcoholized red wine [62], cocoa [63][64][65], and chocolate [66].…”
Section: Flavonoids and Endothelial Functionmentioning
confidence: 91%
“…In this context, FMD represents the current gold standard for the noninvasive measurement of endothelial function in humans. Regarding dietary interventions, various studies previously reported acute and chronic increases in endothelium-dependent vasodilation after the ingestion of flavanol-rich foods͞beverages such as red wine (32), purple grape juice (7), tea (33), cocoa (4,8), and chocolate (34). In most but not in all studies (4), endotheliumdependent vasodilation was measured as FMD by using methodologies comparable to those applied here.…”
Section: Effects Of Flavanol-rich Foods On Vascular Function and No Smentioning
confidence: 99%
“…Results that emanated from these studies corroborate the hypothesis that an increase in NO bioactivity represents the common underlying mechanistic principle for augmented vasodilation. Because of the fact that FMD is almost exclusively mediated by NO (35), increases in NOS activity are principally paralleled by increases in plasma nitroso species (36), and increased vasodilation can be reversed by using NOS inhibition (4,37). Thus, parallel measurements of FMD and circulating NO species, in conjunction with NOS inhibition studies, represent a mechanistically strong experimental framework.…”
Section: Effects Of Flavanol-rich Foods On Vascular Function and No Smentioning
confidence: 99%
See 1 more Smart Citation
“…Flavanol intake improved FMD in hypertensive patients with normal (51) as well as IGT (54). Flavanol-rich cocoa beverage also acutely improved endothelium-dependent vasodilation, platelet function, and circulating bioactive NO in smokers (69,70). In 20 male smokers, dark chocolate, but not white chocolate, improved FMD after 2 h (7.0 vs. 4.4%, p = 0.026), and the effect lasted about 8 h after ingestion (70).…”
Section: Cocoa and Vascular Function: Interventional Studiesmentioning
confidence: 93%